INTEGRATION OF THE HOTEL AND RESTAURANT INDUSTRY OF UKRAINE INTO THE EUROPEAN SPACE - ROMANUKHA, O.; SLASHCHEVA, A.; KHALILOVA- CHUVAEVA, IU. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the state and prospects of Ukraine's cooperation with the European Union in the hotel and restaurant business. It is determined that the beginning of these processes was due to the collapse of the USSR and the need to transform the industry to the requirements of a market economy. Ignoring the fact of global economic polarization threatened the Ukrainian hospitality industry with destruction, and the proximity to one of the world's largest economic centers convinced of the prospects for cooperation. During the tracking of its dynamics, several stages of development were identified. The central place among them belongs to the design of the legal framework. The unification of the legislation not only helped to form the basis for interstate dialogue, but also opened opportunities for dialogue to business representatives and regions. Registration of legal bases intensified work in a number of projects, the most important of which was participation in the TACIS program. It was aimed at supporting the hospitality industry in order to meet the needs of hotels and restaurants around the main transport corridors passing through the territory of Ukraine. This was important for intensifying regional cooperation, holding numerous forums, conferences, meetings, and setting up advisory centers. In turn, the intensification of regional cooperation contributed to investment exchange, the emergence of European hotel and restaurant chains in Ukraine, the transformation of the principles of national hotels and restaurants, improving service, the transition of higher education to European standards in training, organizing their internships in European hospitality. At the moment, we can talk about the conditional accession of the Ukrainian market of hotel and restaurant services to the European and the need to move to the unification of other aspects of cooperation that will open opportunities for investors to work in the Ukrainian market. Among these areas are the need to fight corruption, unify tax legislation, privatize state-owned hotels, and resolve the military conflict in eastern Ukraine.
Keywords: hotel; restaurant; integration; Ukraine; European Union; hospitality